2022
DOI: 10.3389/feart.2022.900866
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying Flood Risk Across the Lower Yellow River Basin, China, Under Shared Socioeconomic Pathways

Abstract: The ecological conservation and high-quality development of the Yellow River basin (YRB) has been adopted as a major national strategy of China. However, the YRB is still afflicted by floods. Here, we proposed a flood risk indicator using direct economic loss degree and improved the SNRD (station-based nonlinear regression downscaling model) and simulated extreme precipitation processes. The correlation coefficient of downscaled average extreme precipitation of CMORPH and CMIP6 data reached 0.817. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…In 2018, the flood risk in Henan Province increased 7.5 times larger than in 2000, while in Shandong Province, it increased 9.2 times larger than 2000 (figure 6(f)). Song et al identified the lower and middle YRB as high-risk areas for future floods, which is in good line with the findings of this current study [46]. In summary, the increased vulnerability of disaster-bearing bodies as well as increased exposure to floods due to socio-economic development had led to an intensification of urban flash flood and flood risk in the YRB.…”
Section: Risk Assessment Of Rainstorm Flood Disasters In the Yrbsupporting
confidence: 91%
See 1 more Smart Citation
“…In 2018, the flood risk in Henan Province increased 7.5 times larger than in 2000, while in Shandong Province, it increased 9.2 times larger than 2000 (figure 6(f)). Song et al identified the lower and middle YRB as high-risk areas for future floods, which is in good line with the findings of this current study [46]. In summary, the increased vulnerability of disaster-bearing bodies as well as increased exposure to floods due to socio-economic development had led to an intensification of urban flash flood and flood risk in the YRB.…”
Section: Risk Assessment Of Rainstorm Flood Disasters In the Yrbsupporting
confidence: 91%
“…Meanwhile, The YRB holds significant importance as an essential grain-producing area in China, playing an indispensable role in socioeconomic development and ecological conservation within the country. Recognizing its importance, the ecological conservation and high-quality development of the YRB has been adopted as a major national strategy of China [46]. However, the YRB is still afflicted by floods.…”
Section: Introductionmentioning
confidence: 99%